2015
DOI: 10.1080/10803548.2015.1035921
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal problems and quality of life of elementary school teachers

Abstract: The results reveal high prevalence of MSP among teachers, as well as its negative impacts on QoL. Especially neck and lower back seem to be the most frequently affected regions of the body. These findings draw attention toward the need for developing strategies to prevent MSP among teachers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
22
5
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 27 publications
9
22
5
8
Order By: Relevance
“…Though, studies that reported prevalence rate of SNP are distinctively scant. [12, 16, 21] The findings of this study is similar to a study done among Malaysian school teachers reporting 60% prevalence [22] . However, the prevalence of this study is higher than the studies conducted in China (48.7%) [12], Saudi Arabia (45.2%) [23], Japan (35.4%) [24] and Brazil (31.6%) [25] .…”
Section: Discussionsupporting
confidence: 88%
“…Though, studies that reported prevalence rate of SNP are distinctively scant. [12, 16, 21] The findings of this study is similar to a study done among Malaysian school teachers reporting 60% prevalence [22] . However, the prevalence of this study is higher than the studies conducted in China (48.7%) [12], Saudi Arabia (45.2%) [23], Japan (35.4%) [24] and Brazil (31.6%) [25] .…”
Section: Discussionsupporting
confidence: 88%
“…In the past 12 months, 48% of the teachers presented musculoskeletal symptoms (Table 2). Our findings corroborate with other research on basic education teachers, which showed high prevalence of musculoskeletal symptoms in teachers, ranging from 40% to 95% [18][19][20][21][22][23] . The parts of the body most affected by musculoskeletal symptoms were the knees, ankles and/or feet, neck, wrists/ hands and back (Table 2).…”
Section: Discussionsupporting
confidence: 92%
“…Other studies have also found a high prevalence of absences due to musculoskeletal symptoms located in the same regions highlighted in this survey in basic education teachers 2,19,21 . Today, the teaching profession is regarded as one of the most stressful professions 26 .…”
Section: Discussionsupporting
confidence: 74%
“…Among the categories, musculoskeletal disorders, as expected, were the most frequent ones (88.3%). This prevalence was relatively higher compared with results from other studies conducted among school teachers (16,17,24,25).…”
Section: Discussioncontrasting
confidence: 68%